2010
DOI: 10.1186/1471-2180-10-178
|View full text |Cite
|
Sign up to set email alerts
|

The proline-rich peptide Bac7(1-35) reduces mortality from Salmonella typhimurium in a mouse model of infection

Abstract: BackgroundBac7 is a proline-rich peptide with a potent in vitro antimicrobial activity against Gram-negative bacteria. Here we investigated its activity in biological fluids and in vivo using a mouse model of S. typhimurium infection.ResultsThe efficacy of the active 1-35 fragment of Bac7 was assayed in serum and plasma, and its stability in biological fluids analyzed by Western blot and mass spectrometry. The ability of the peptide to protect mice against Salmonella was assayed in a typhoid fever model of inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
59
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 26 publications
2
59
1
Order By: Relevance
“…S1), which points to the C-terminally truncated peptides [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Api88 and 1-16 Api88, respectively. The peak area of [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Api88 increased very rapidly during the first 30 min to 70% of the initial peak area of Api88 and then showed a further slight increase to 80% within the next 30 min, before decreasing slowly afterwards (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S1), which points to the C-terminally truncated peptides [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Api88 and 1-16 Api88, respectively. The peak area of [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Api88 increased very rapidly during the first 30 min to 70% of the initial peak area of Api88 and then showed a further slight increase to 80% within the next 30 min, before decreasing slowly afterwards (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…All these studies have confirmed a very low toxicity in mice and high efficacies in different murine infection models, with peptide doses typically below 10 mg/kg of body weight (BW) (8,18). Recently, we were able to extend the activity of apidaecin 1b, an 18-residue-long PrAMP expressed in honey bees, toward K. pneu-moniae and P. aeruginosa, by modifying two residues and both termini (19).…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Their importance in innate host defense has been clearly demonstrated in several in vivo knockout models, where loss of HDP expression was shown to result in an increased susceptibility to infections (4)(5)(6). In addition, administration of HDPs was shown to have a protective effect in multiple in vivo infection models (7)(8)(9). Because of this strong protective activity, therapeutic use of HDPs as anti-infectives has gained great interest in both human and veterinary medicine (10).…”
mentioning
confidence: 99%
“…Insect-derived PrAMPs, e.g., abaecin, apidaecin, drosocin, and pyrrhocoricin (4,5,7,23), are typically 20 to 35 residues long and have a relatively high proportion of basic amino acid residues. Recently, several laboratories have started to optimize PrAMPs for clinical applications, e.g., A3-APO (25), Bac7 (12), oncocin (16), and Api88 (9), which proved successful in rodent infection models (1,15,32). Mechanistically, PrAMPs and the related designer peptides enter the bacteria and kill them, most likely by inhibiting the 70-kDa bacterial chaperone DnaK (17,20,24).…”
mentioning
confidence: 99%